Studi Hubungan Nilai Uniaxial Compressive Strength dan Nilai Schmidt Hammer Batulempung pada Formasi Balikpapan dan Kampungbaru Daerah Kutai Kartanegara, Provinsi Kalimantan Timur - Amarullah Amarullah; Albertus Juvensius Pontus; Shalaho Dina Devy; Revia Oktaviani; Tommy Trides; Rety Winonazada (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Compressive strength is one of the mechanical properties of rock behavior. This study focuses on the Balikpapan and Kampungbaru Formations located in the Kutai Kartanegara area, East Kalimantan. The Schmidt Hammer testing method was applied due to the lack of previous studies utilizing this tool to evaluate rock hardness in correlation with compressive strength. The research site is situated in the Kutai Kartanegara area, specifically in the districts of Muara Badak, Muara Jawa, and Sanga-Sanga. Field observations revealed the presence of claystone slopes at predetermined locations. Based on the test results, the uniaxial compressive strength (UCS) values for the Balikpapan Formation range from 3.453 MPa to 5.454 MPa, while the Kampungbaru Formation ranges from 3.317 MPa to 8.571 MPa. The Schmidt Hammer rebound number (RN) values for the Balikpapan Formation range from 17 to 19.6, and for the Kampungbaru Formation from 15 to 23.7. A negative correlation was found between the rebound number and UCS, where higher RN values tend to correspond with lower UCS values. This is supported by the linear regression analysis showing a negative coefficient (-0.450).